PENERAPAN PROGRAM MURAJAAH JUZ 30 DALAM MENINGKATKAN HAFALAN DAN AKHLAK SISWA DI SDIT SEMARAK - Bakti Komala Sari; Rio Mezionto; Legi Hovera; Rianto (CV. KAMPUS AKADEMIK PUBLISING, 2023)
To find out the implementation of the Murajaah Juz 30 Program at SDIT Semarak Rejang Lebong, to find out the improvement of students' memorization and morals through the implementation of the Murajaah Juz 30 Program at SDIT Semarak Rejang Lebong. In this study using, qualitative research by means of a description approach. This research uses a type of field research method (field research). The research subjects were school principals, teachers who manage the honesty canteen, and SDIT Semarak students. Based on the analogy of a snowball, which starts with a small snowball and then swells gradually because there is an accumulation of snow when it is rolled over the snow. It starts with a number of people or problems, then expands to the relationship with the respondent. This research is qualitative with a theological approach. The data source in this study is the subject where the data is obtained. In this study, researchers used two types of data sources, namely primary data and secondary data. Collecting data in accordance with the objectives of the researcher, namely observation, interviews and documentation. Data analysis used by researchers in this study was carried out through three stages, namely: data reduction, data presentation, data verification/drawing conclusions. By implementing the murajaah juz 30 program at SDIT Semarak Rejang Lebong, it has improved the quality of students' memorization and morals, both in behavior in the school environment and the environment where they live. Supporting factors in implementing the murajaah juz 30 program at SDIT Semarak Rejang Lebong are human resources, infrastructure and students. The inhibiting factor in murajaah juz 30 is that there are still many students who have not focused on activities, especially lower grade students, and there is no juz amma book to hold students' handbook for memorizing at home.